Penerapan Learning by the Case Method terhadap Efektivitas Pembelajaran Mahasiswa Akuntansi UIN Jakarta - Yessi Fitri; Ela Patriana (Akuntabilitas, 2022)
The main issue of this research is the Learning by the Case Method (LCM) application to the learning effectiveness of accounting student Syarif Hidayatullah Jakarta. The purpose of this research is to obtain empirical evidence on the effect of the application of LCM on the effectiveness of learning of UIN accounting student Syarif Hidayatullah Jakarta with intellectual intelligence and emotional intelligence as moderating variables. The respondents in this research were accounting student classes of 2016, 2017, and 2018 with purposive sampling. The hypothesis testing method uses Moderated Regression Analysis. The results showed the application of LCM had a positive effect on the effectiveness of accounting students' learning. Intellectual intelligence and emotional intelligence don’t moderate the effect of the application of LCM on the effectiveness of accounting learning.